Resolusi Konflik Pertanahan antara Hak Ulayat Masyarakat Adat Kampung Doyo Lama terhadap Kawasan Hutan Produksi Konversi di Kabupaten Jayapura - Leni Sipra Helen Rahakbauw (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study discusses land conflicts between the customary rights of the indigenous people of Kampung Doyo Lama and the Conversion Production Forest (HPK) area in Jayapura Regency. Conflicts occur due to the disharmonization of agrarian law and forestry law regulations that cause overlapping claims between the state and indigenous peoples. This research uses a normative juridical approach with a legislative and conceptual approach. The results of the study show that normative recognition of customary rights has not been followed by effective legal protection in practice. Conflict resolution requires an approach to legal pluralism and restorative justice through the recognition of customary law, multi-stakeholder mediation, indigenous peoples' participation and harmonization of land and forestry policies to realize substantive justice for indigenous Papuans.